Oxytocin and serotonin in the modulation of neural function: Neurobiological underpinnings of autism-related behavior - Zhao, Feng; Zhang, Hao; Wang, Peng; Cui, Wenjie; Xu, Kaiyong; Chen, Dan; Hu, Minghui; Li, Zifa; Geng, Xiwen; Wei, Sheng (Frontiers in Neuroscience, 2022)
Autism spectrum disorders (ASD) are a group of generalized neurodevelopmental disorders with primary clinical features including social communication disorder and repetitive stereotyped behavioral interest. The abnormal structure and function of the brain network is the basis of social dysfunction and stereotyped performance in patients with ASD. The number of patients diagnosed with ASD is increasing annually, but there remains a lack of effective intervention and treatment. Oxytocin has been revealed to effectively improve social cognitive function and significantly improve the social information processing, empathy, and social communication abilities of patients with ASD. Changes in serotonin levels have also been reported to affect the development of the brain and causes ASD-like behavioral abnormalities, such as anxiety, depression-like behavior, and stereotyped behavior. The present review will focus on the research progress of serotonin and oxytocin in the pathogenesis, brain circuit changes, and treatment of ASD. Revealing the regulatory effect and neural mechanisms of serotonin and oxytocin in patients with ASD is not only conducive to a deeper comprehension of the pathogenesis of ASD, but also has vital clinical significance.